Meta Analysis on the Effect of the Quality of Health Services with the Level of Patient Satisfaction - Munawaroh, Siti Mar'atul; Nurhayati, Happy; Sudarmono, Andang; Dhony, Ervia Fahma; Veibiani, Nindita Arum; Krisnawati, Hesthi; Puspita, Wita Hana; Handayani, Dian; Dianika, Bani; Sumarah, Kristuti Catur (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: patient-oriented health services are the primary strategy for health service organizations. A good service is determined by the fact that the services provided can meet the patient's needs. Patient satisfaction is an integral part of the quality assurance of health service. This study aims to analyze the quality of tangible health services with patient satisfaction in receiving health services.Subjects and Method: Meta-analysis was performed by searching journals from direct databases such as Google Scholar, Science Direct, and PubMed using the keywords service quality, patient satisfaction, and heat service. The inclusion criteria in this study were full text from 2010-2021, with a cross-sectional study. The data analysis was carried out by RevMan 5.3.Results: Nine articles have been analyzed, showing that the quality of service had direct evidence of an effect on patient satisfaction in accessing health services (aOR= 4.17; 95% CI= 1.78 to 9.78; p <0.001).Conclusion: The quality of direct evidence (tangible) affects patient satisfaction in accessing health services.Keywords: tangible, service, patient satisfaction.Correspondence: Siti Mar'atul Munawaroh. Ahmad Dahlan University. Jl. Prof. Dr. Soepomo, Janturan, Umbulharjo, Yogyakarta. Email: sitimaratul08@gmail.com. Mobile +6282133295468.Journal of Health Policy and Management (2021), 06(02): 107-115https://doi.org/10.26911/thejhpm.2021.06.02.03